Education for the unified health system: what do good professors do from the perspective of students? - do Carmo Menegaz, Jouhanna; Schubert Backes, Vânia Marli (Investigación y Educación en Enfermería, 2015)
Objective. to analyze the educational practices for the Unified Health System performed by good professors, from the perspective of nursing, medical and odontology students, based on the Shulman’s concepts of knowledge of educational ends, purposes, values and their historical and philosophical grounds, at a university in southern Brazil. Methods. A qualitative study with an exploratory and analytical approach in which the participants were graduating students, interviewed with the aid of vignettes, between October of 2011 and January of 2012. Data were analyzed based on thematic analysis. Results. it was observed that good professors educate for the Unified Health System through the promotion of teamwork, interdisciplinary practices, good communication, leadership exercises, and promotion of a student’s desire to be an agent of change for the sake of improvement and guaranteeing the right to health. Conclusion. the students attribute to professors the responsibility for the performance of these practices. Despite their consistency with the Brazilian curriculum guidelines, the professors that perform them are seen as a minority. How to cite this article: Menegaz JC, Backes VMS. Education for the unified health system: what do good professors do from the perspective of students? Invest Educ Enferm. 2015; 33(3):